Efisiensi Perolehan Pendapatan Antara Beban Yang Dikeluarkan Dengan Pendapatan Terhadap Keuntungan Usaha Menggunakan Metode Target Costing (Studi Pada Usaha Kuliner Jajanan Najla Di Purwakarta) - Puspasari, Dewi; Neng Salwa; Herrenauw, Laura Silvana; Rosa Rosadiana (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2024)
The magnitude of profit obtained is highly dependent on production cost efficiency, thus requiring special attention to achieve the company's target. Cost control must align with the company's objectives, including achieving maximum profit with minimal production costs. This study aims to analyze the relationship between expenses, income, and business profits in UMKM Jajanan Nazla, as well as identify key factors influencing the efficiency of revenue generation and expense expenditure. Based on the analysis of production costs, UMKM Jajanan Nazla faces a deficit in net profit due to the inability to cover production costs. Therefore, this research applies the target costing method to improve its profitability. The steps of implementing target costing involve determining market prices, calculating target profits, and identifying target production costs. By implementing value engineering, such as reducing packaging costs, labor costs, and even eliminating rental costs, UMKM successfully reduces production costs to meet the set target cost. As a result, production costs decreased from Rp. 7,880,000 to Rp. 5,240,000 per month, resulting in savings of Rp. 2,640,000. Thus, the initially deficit net profit increased to Rp. 1,510,000 per month after the application of target costing. In conclusion, it can be inferred that the target costing method is effective in improving the production cost efficiency of UMKM Jajanan Nazla, helping them strengthen their position in the competitive market.